Localized temperature and pressure measurements inside CS2-filled fiber using stimulated Brillouin scattering - Popp, Alexandra; Geilen, Andreas; Walter, Daniel; Chemnitz, Mario; Junaid, Saher; Poulton, Christopher G.; Marquardt, Christoph; Schmidt, Markus A.; Stiller, Birgit (2021 Conference on Lasers and Electro-Optics Europe and European Quantum Electronics Conference, CLEO/Europe-EQEC 2021, 2021)
Liquid-core fibers are a versatile platform for nonlinear light-matter interactions, combining highly nonlinear materials like carbon disulfide (CS 2 ) or nitrobenzene with the confinement and long interaction length of optical fibers. While there is only minor influence of strain inside the fiber core due to the liquid phase, pressure effects have a dominant role depending on the thermodynamic regime and filling of the fiber core [1]. In our experiments we use Brillouin Optical Correlation Domain Analysis (BOCDA) to create a localized Brillouin response [2]. Due to the associated refractive index change, this response is strain, pressure and temperature dependent. While the discrimination of strain and temperature effects in silica fibers is complicated due to the combined Brillouin response [3] , CS 2 filled fibers have the advantage of thermo- and piezo-optical coefficients with different signs. While the thermo-optic coefficient is negative, resulting in a downshifted acoustic response for higher temperature, the piezo-optic coefficient is positive, resulting in an upshifted Brillouin frequency for increased pressure. To investigate the response of the CS 2 , we heated different parts of the 60cm liquid-core fiber on a hotplate up to a temperature of 135 C while measuring the distributed Brillouin response with a resolution of 4cm.
CRIS-Team Scopus Importer:2021-10-29